Contribution of oil palm towards self sufficiency in vegetable oil production in Telangana: An analysis : Contribution of oil palm towards self sufficiency in vegetable oil production in Telangana: An analysis - RAJASEKHAR MARRI; BOGA NEERAJA PRABHAKAR; ARAVA BHAGWAN; G VIJAYA KRISHNA (Journal of Oilseeds Research, 2023)
Oil palm as a crop is new to several districts of Telangana but the state ranks 6th in area, 2nd in production of oil palm in the country, while it ranks 1st in Oil Extraction Rate (19.22%) which is a model for fixing FFB price. Twenty six districts were identified suitable for the crop. After the introduction of oil palm in the state barely 10 years ago, the area has reached to 37,485 ha by the end of Vanakalam (Kharif) 2022. More area is coming up in Yesangi (Rabi) 2022, thus the area under oil palm should hopefully cross 80,000 ha by the end of 2022-23 season raising Telangana State to 2nd position in India (Department of Horticulture, 2021). With respect to edible oils, groundnut, sesame, soybean, sunflower and safflower are the edible oilseed crops cultivated in Telangana (Department of Food and Public Distribution, GOI, 2021), The annual per capita consumption of edible oil in Telangana was 14.64 L in the year 2016 (Food Consumption Pattern in Telangana State– 2017), the annual requirement of edible oils is 0.51 million MT (calculated based on a population of 35 million).